A meta-synthesis of qualitative research on perceptions of people with long-term neurological conditions about group-based memory rehabilitation - das Nair, Roshan; Martin, Kristy-Jane; Sinclair, Emma (Routledge Open Select, 2014)
The effectiveness of memory rehabilitation based on randomised controlled trials and meta-analyses has been inconclusive, but patient reports based on qualitative studies have been largely positive. We conducted a meta-synthesis of qualitative studies of group-based memory rehabilitation programmes for people with neurological conditions. Based on systematic searches of electronic databases and reference lists, five papers (87 participants) were selected. Quality appraisal of papers was conducted by two independent reviewers using the Critical Appraisal Skills Programme tool. Data synthesis was guided by the meta-ethnography approach. Fiver higher order themes were elicited. These suggested that memory rehabilitation was associated with insight and acceptance of participants’ neurological condition and resultant cognitive deficits. The therapeutic effects of the groups, with social support and leisure activities, helped with participants’ confidence. There were improvements in memory related to better self-awareness and learning to use new skills and strategies to compensate for memory deficits. These improvements also related to other psychological effects, in terms of positively affected mood, confidence and fatigue. Ultimately, these changes had a positive impact on daily life, with changes seen in the personal, inter-personal and professional spheres. Therefore, this synthesis of qualitative studies suggests that memory rehabilitation offers positive outcomes for people with long-term neurological conditions.